An Overview of Challenges Limiting the Design of Protective Mucosal Vaccines for Finfish - Munang’andu, Hetron Mweemba; Mutoloki, Stephen; Evensen, Øystein (Frontiers in Immunology, 2015)
Research in mucosal vaccination in finfish has gained prominence in the last decade in pursuit of mucosal vaccines that would lengthen the duration of protective immunity in vaccinated fish. However, injectable vaccines have continued to dominate in the vaccination of finfish because they are perceived to be more protective than mucosal vaccines. Therefore, it has become important to identify the factors that limit developing protective mucosal vaccines in finfish as an overture to identifying key areas that require optimization in mucosal vaccine design. Some of the factors that limit the success for designing protective mucosal vaccines for finfish identified in this review include the lack optimized protective antigen doses for mucosal vaccines, absence of immunostimulants able to enhance the performance of non-replicative mucosal vaccines, reduction of systemic antibodies due to prolonged exposure to oral vaccination and the lack of predefined correlates of protective immunity for use in the optimization of newly developed mucosal vaccines. This review also points out the need to develop prime-boost vaccination regimes able to induce long-term protective immunity in vaccinated fish. By overcoming some of the obstacles identified herein it is anticipated that future mucosal vaccines shall be designed to induce long-term protective immunity in finfish.